ENERGY AND PROTEIN REQUIREMENTS FOR PEKIN DUCKS (Anas platyrhynchos) IN PHASES OF GROWTH AND FINISHING - Gallo, Magdalena Herrera (2009)
With the purpose of getting to know the energy and protein required by the Pekin duck (Anas platyrhinchos) in growth and finishing phases, isoenergetic and isoproteic diets were used, five treatments with four repetitions for the energy and the equal form for the protein. The variables studied were: consumption of food, gain of weight, nutritious conversion and yield to the channel. In the growing phase significant differences in the variable gain of weight and nutritious conversion was registered. It didn’t seize in the food consumption. Although, it was observed that the best consumption of food, gain of weight and nutritious conversion, were achieved, with 3010 kcal EM kg-1 and 22% PB (T3), based on the energy and with 2975 kcal EM kg-1 and 19% PB based on the protein, respectively. In the finishing phase, significant differences among the treatments were not registered, however, based on the energy, the treatment with 2833 kcal EM kg-1 and 18% PB (T2) registered the best answers in the productive variables as well as the diet with 2991 kcal EM kg-1 and 18 PB (T5) based on the protein.